2010
DOI: 10.2174/187152410793429764
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Heme Oxygenase-1 in Cerebral Ischemia

Abstract: Cerebral ischemia is one of the leading causes of death and disability in industrialized countries, with no curative treatments to date. Identification of potential targets and elucidation of their physiological role under stress conditions may give support to the development of drugs and strategies to contend with this pathology. In the last years, Heme oxygenase-1 (HO-1) has been considered by many groups as a potential target in ischemic damage. HO-1 is the enzyme responsible for the conversion of the heme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…Reportedly, Hmox1 plays a protective role via its heme catabolism products in cerebral ischemia, cardiac ischemia, limb I/R, hepatic I/R, as well as transplantation that involves I/R events. 21 We found that Hmox1 was significantly upregulated in both cortex and striatum of I/R mice at 2, 8, and 24 hours post I/R. Although this result was inconsistent with previous studies, 21,22 Hmox1 might take part in the development of cortex and striatum injury after cerebral I/R.…”
Section: Article In Presscontrasting
confidence: 80%
“…Reportedly, Hmox1 plays a protective role via its heme catabolism products in cerebral ischemia, cardiac ischemia, limb I/R, hepatic I/R, as well as transplantation that involves I/R events. 21 We found that Hmox1 was significantly upregulated in both cortex and striatum of I/R mice at 2, 8, and 24 hours post I/R. Although this result was inconsistent with previous studies, 21,22 Hmox1 might take part in the development of cortex and striatum injury after cerebral I/R.…”
Section: Article In Presscontrasting
confidence: 80%
“…HO-1 is a neuroprotective enzyme that exhibits anti-oxidative and anti-inflammatory effects (Aztatzi-Santillan et al, 2010; Bae et al, 2010). HO-1 mRNA and protein expression increase in the brain of mice after TBI (Anderson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…HO-1 plays a neuroprotective role in other pathophysiological conditions including; 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridinium (MPP+) neurotoxicity (Bae et al, 2010), and stroke (Shah et al, 2010). Disrupting endogenous HO-1 responses has been associated with poor outcomes in many central nervous system disorders (Aztatzi-Santillan et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…185 There is no doubt that there is an important protective role for HOs in ICH, but mice studies have proven less than definitive as to the relative roles of the constitutively expressed heme oxygenase-2 (HO2) and the readily induced HO1. For example, HO2 ko mice appear to be more susceptible to damage after ICH than HO1 ko mice, 186,187 whereas HO1 deficiency leads to more damage in an ischemic stroke mouse model than does HO2 deficiency.…”
Section: B Hpx In Brain Injury and Neurodegenerative Diseasesmentioning
confidence: 99%